Estimation of the preservation effectiveness of the removed tooth duct using PRP and PRF technique according to laser-correlation spectrometry - Zahradska, O. L.; Maximenko, P. V.; Kirichek, O. V. (Journal of Education, Health and Sport, 2017)
The purpose of this work was to evaluate the effectiveness of some modern methods of preservation of the hole, aimed at preserving the tissues of the alveolar process of the jaws immediately after tooth extraction. Clinical studies were conducted in 69 patients with planned indications for tooth extraction, after which the tooth well was either not subjected to additional interventions, or was filled with a composition of PRP and Kollapan or a clot of PRF. The effectiveness of the effects was evaluated according to laser correlation spectrometry, which showed the best regeneration in the PRF well of the clot.